The Influence of Workplace Spirituality, Job Satisfaction, and Organizational Culture on Employee Performance at Niagara Swalayan - Hidayat, Ricki; Talim, Margaretha Banowati (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the effects of workplace spirituality, job satisfaction, and organizational culture on employee performance at Niagara Swalayan. This study is explanatory quantitative research with data collection using Likert - scale questionnaire and employee performance assessment of 73 respondents out of a total population of 89 people. The data analyzed by using SPSS 25 program. The results of this study indicate that workplace spirituality and organizational culture have a positive and significant effect on employee performance at Niagara Swalayan. Meanwhile, job satisfaction does not have a significant effect on employee performance at Niagara Swalayan. Based on the detailed information obtained from respondents concerning job satisfaction, it is known that routine and structured nature of work activities, economic needs, and a sense of comfort in the work environment are the main reasons why employees continue to perform well despite experiencing job dissatisfaction.